Degradable environment-friendly material cosmetic packaging bottle and preparation method thereof

By adding hydroxy quaternary ammonium salt grafted polylactic acid and maleic anhydride grafted polyethylene to the materials for cosmetic packaging bottles, the problems of poor mechanical properties, non-anti-bacterial and non-degradable polyethylene are solved, and the problem of polyethylene materials is not good, and the problem of more than 100% polyethylene materials is prepared. Degradable environmentally friendly materials with high mechanical properties and significant antibacterial properties.

CN119410051AInactive Publication Date: 2025-02-11ZHEJIANG RONGYI PACKAGING TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411577061.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyethylene materials for cosmetic packaging bottles have poor mechanical properties and are not antibacterial and degradable.

Method used

Using 60-75 parts by weight of polyethylene resin, 25-40 parts by weight of hydroxy quaternary ammonium salt grafted polylactic acid, 1.6-3 parts by weight of maleic anhydride grafted polyethylene and 0.3-0.6 parts by weight of antioxidant, the mixture was mixed by melt blending. Extrusion granulation process prepares degradable environmentally friendly materials for the production of cosmetic packaging bottles.

Benefits of technology

It improves the mechanical properties of degradable environmentally friendly materials, enhances its antibacterial rate against E. coli and Staphylococcus aureus, and achieves better application of materials in cosmetic packaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention relates to the technical field of plastic packaging bottles, and discloses a degradable environment-friendly material cosmetic packaging bottle and a preparation method thereof.The degradable environment-friendly material is prepared from, by weight, 60-75 parts of polyethylene resin, 25-40 parts of hydroxyl quaternary ammonium salt grafted polylactic acid, 1.6-3 parts of maleic anhydride grafted polyethylene and 0.3-0.6 part of antioxidant; the maleic anhydride grafted polyethylene disclosed by the invention can be used as a compatilizer to improve the compatibility between the hydroxyl quaternary ammonium salt grafted polylactic acid and polyethylene resin, the obtained degradable environment-friendly material has higher mechanical properties, and the hydroxyl quaternary ammonium salt grafted polylactic acid contains biquaternary ammonium salt antibacterial groups, so that the antibacterial property of the degradable environment-friendly material is improved. Therefore, the degradable environment-friendly material shows good antibacterial performance. The degradable environment-friendly material disclosed by the invention contains a degradable polylactic acid component, is green, environment-friendly, degradable and good in antibacterial property, and has good application in the aspects of cosmetic packaging bottles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic packaging bottles, in particular to a cosmetic packaging bottle made of degradable and environmentally friendly materials and a preparation method thereof. Background Art

[0002] Polyethylene is non-toxic and odorless, has good solvent resistance, low water absorption, and low cost. It has important applications in cosmetic packaging bottles, food packaging, containers, etc. However, in recent years, the excessive use of petroleum-based polymers such as polyethylene has caused serious white pollution problems. The development of green and degradable polymer materials is a research trend. Such as polylactic acid, polyethylene terephthalate, polycaprolactone, etc.

[0003] Polylactic acid has good mechanical properties, is biodegradable, and is widely used. By compounding polylactic acid with plastics such as polyethylene and polypropylene, a degradable alloy material with better performance can be obtained. The invention patent with announcement number CN107722581B discloses a polylactic acid alloy foam material with a high foaming ratio and a preparation method thereof. With polylactic acid resin and polyethylene resin as raw materials, the alloy foam material obtained by melt blending has the advantages of good viscoelasticity and high foaming ratio. However, the compatibility between polylactic acid and polyethylene is poor, and a compatibilizer is usually required to be added to obtain an alloy composite material with better performance. In addition, traditional polyethylene packaging materials do not have antibacterial properties, which is not conducive to their practical applications in cosmetic packaging, food and drug packaging, etc. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a cosmetic packaging bottle made of degradable and environmentally friendly material and a preparation method thereof, thereby solving the problems of poor mechanical properties of polyethylene materials used for cosmetic packaging bottles and lack of antibacterial and degradable properties.

[0005] The technical solution provided by the invention is: a degradable environmentally friendly material comprising 60-75 parts by weight of polyethylene resin, 25-40 parts by weight of hydroxy quaternary ammonium salt grafted polylactic acid, 1.6-3 parts by weight of maleic anhydride grafted polyethylene, and 0.3-0.6 parts by weight of antioxidant.

[0006] The preparation method of hydroxy quaternary ammonium salt grafted polylactic acid comprises the following steps: adding polylactic acid and styryl hydroxy quaternary ammonium salt into chloroform, heating to 50°C, stirring to dissolve, and then performing reduced pressure distillation to remove the chloroform, adding the mixture and dicumyl peroxide into a torque rheometer to perform melt grafting, adding the cooled product into chloroform, heating to 50°C, stirring to dissolve, and then performing reduced pressure distillation until a large amount of precipitates are precipitated, filtering, and drying to obtain the hydroxy quaternary ammonium salt grafted polylactic acid.

[0007] The structural formula of styryl hydroxy quaternary ammonium salt is as follows: .

[0008] Furthermore, the masses of styryl hydroxy quaternary ammonium salt and dicumyl peroxide are 3-12% and 0.2-0.1% of the mass of polylactic acid, respectively.

[0009] Furthermore, the temperature during melt grafting is 175-185° C., and the time is 5-10 min.

[0010] Further, the preparation method of styryl hydroxy quaternary ammonium salt comprises: Step (1), add 2,3-epoxypropyltrimethylammonium chloride and diethanolamine to ethanol, heat to 45-60°C, stir and react for 6-12 hours, and remove low boiling points by distillation under reduced pressure to obtain an intermediate. The reaction formula is:

[0011] Step (2), add the intermediate, 4-chloromethylstyrene, to acetonitrile, heat to 70-80°C, stir and react for 18-24h, distill under reduced pressure, dissolve the product in ethanol and recrystallize to obtain styryl hydroxy quaternary ammonium salt. The reaction formula is:

[0012] Furthermore, the mass of diethanolamine in step (1) is 70-78% of 2,3-epoxypropyltrimethylammonium chloride.

[0013] Furthermore, in step (2), the mass of 4-chloromethylstyrene is 60-75% of the mass of the intermediate.

[0014] Furthermore, a method for preparing a degradable environmentally friendly material comprises: mixing polyethylene resin, hydroxyl quaternary ammonium salt grafted polylactic acid, maleic anhydride grafted polyethylene, and an antioxidant, adding them into a twin-screw extruder for extrusion granulation, the temperature of the extruder sections 1-7 is 125-190°C, and obtaining a degradable environmentally friendly material.

[0015] Furthermore, a degradable and environmentally friendly material cosmetic packaging bottle is prepared using degradable and environmentally friendly materials, and the degradable and environmentally friendly materials are hot-pressed in a mold to obtain a degradable and environmentally friendly material cosmetic packaging bottle.

[0016] The technical effect of the present invention is as follows: 2,3-epoxypropyltrimethylammonium chloride, diethanolamine and 4-chloromethylstyrene are used as reactants to prepare a styrene-based hydroxyl quaternary ammonium salt containing a diquaternary ammonium salt group and multiple hydroxyl groups, which is then melt-grafted with polylactic acid to obtain hydroxyl quaternary ammonium salt-grafted polylactic acid, and finally melt-blended and extruded with polyethylene resin and maleic anhydride-grafted polyethylene to obtain a degradable and environmentally friendly material.

[0017] The hydroxyl quaternary ammonium salt grafted polylactic acid of the invention contains a large number of hydroxyl groups, which can react with the anhydride groups of the maleic anhydride grafted polyethylene, so that the maleic anhydride grafted polyethylene can be used as a compatibilizer to improve the compatibility between the hydroxyl quaternary ammonium salt grafted polylactic acid and the polyethylene resin, so that the degradable and environmentally friendly material formed by the polyethylene and the polylactic acid has higher mechanical properties and shows better tensile strength and flexural strength.

[0018] The hydroxy quaternary ammonium salt grafted polylactic acid of the invention contains a diquaternary ammonium salt antibacterial group, which significantly improves the antibacterial rate of the degradable environmentally friendly material to Escherichia coli and Staphylococcus aureus, and exhibits good antibacterial performance.

[0019] The degradable and environmentally friendly material of the present invention contains a degradable polylactic acid component, is green, environmentally friendly, degradable, and has good antibacterial performance, and has good practical applications in cosmetic packaging bottles and the like. DETAILED DESCRIPTION

[0020] In order to understand the technical features and contents of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described here.

[0021] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0022] Polyethylene resin, Suzhou Jishao Engineering Plastics Co., Ltd.

[0023] Maleic anhydride grafted polyethylene, Guangzhou Jinkai Chemical Co., Ltd.

[0024] Polylactic acid, Shenzhen Xingkaiyue Biotechnology Co., Ltd.

[0025] Example 1 Step (1), add 3 g of 2,3-epoxypropyltrimethylammonium chloride and 2.34 g of diethanolamine to 50 mL of ethanol, heat to 45° C., stir to react for 12 h, and remove low-boiling substances by distillation under reduced pressure to obtain an intermediate.

[0026] Step (2), add 2 g of the intermediate and 1.3 g of 4-chloromethylstyrene to 30 mL of acetonitrile, heat to 80° C., stir and react for 24 h, distill under reduced pressure, dissolve the product in ethanol and recrystallize to obtain styryl hydroxy quaternary ammonium salt.

[0027] Step (3), add 40g of polylactic acid and 3g of styryl hydroxy quaternary ammonium salt to 500mL of chloroform, heat to 50°C, stir to dissolve, and then distill under reduced pressure to remove chloroform, add the mixture and 0.25g of diisopropylbenzene peroxide to a torque rheometer, perform melt grafting at 185°C for 5min, add the cooled product to chloroform, heat to 50°C, stir to dissolve, and then distill under reduced pressure until a large amount of precipitate is precipitated, filter and dry to obtain hydroxy quaternary ammonium salt grafted polylactic acid.

[0028] Step (4), 750g polyethylene resin, 250g hydroxy quaternary ammonium salt grafted polylactic acid, 16g maleic anhydride grafted polyethylene, and 6g antioxidant 1076 are mixed and added into a twin-screw extruder for extrusion granulation. The temperatures of sections 1-7 of the extruder are 125°C, 155°C, 180°C, 175°C, 185°C, 190°C, and 190°C to obtain a degradable and environmentally friendly material.

[0029] Example 2 Step (1), add 3 g of 2,3-epoxypropyltrimethylammonium chloride and 2.1 g of diethanolamine to 35 mL of ethanol, heat to 50° C., stir to react for 12 h, and remove low-boiling substances by distillation under reduced pressure to obtain an intermediate.

[0030] Step (2), add 2 g of the intermediate and 1.5 g of 4-chloromethylstyrene to 40 mL of acetonitrile, heat to 70° C., stir and react for 24 h, distill under reduced pressure, dissolve the product in ethanol and recrystallize to obtain styryl hydroxy quaternary ammonium salt.

[0031] Step (3), add 40g of polylactic acid and 1.2g of styryl hydroxy quaternary ammonium salt to 400mL of chloroform, heat to 50°C, stir to dissolve, and then distill under reduced pressure to remove chloroform, add the mixture and 0.08g of diisopropylbenzene peroxide to a torque rheometer, perform melt grafting at 175°C for 10min, add the cooled product to chloroform, heat to 50°C, stir to dissolve, and then distill under reduced pressure until a large amount of precipitate is precipitated, filter and dry to obtain hydroxy quaternary ammonium salt grafted polylactic acid.

[0032] Step (4), 680g polyethylene resin, 320g hydroxy quaternary ammonium salt grafted polylactic acid, 22g maleic anhydride grafted polyethylene, and 4g antioxidant 1076 are mixed and added into a twin-screw extruder for extrusion granulation. The temperatures of sections 1-7 of the extruder are 125°C, 155°C, 180°C, 175°C, 185°C, 190°C, and 190°C to obtain a degradable and environmentally friendly material.

[0033] Example 3 Step (1), add 3 g of 2,3-epoxypropyltrimethylammonium chloride and 2.1 g of diethanolamine to 35 mL of ethanol, heat to 60° C., stir to react for 6 h, and remove low boiling points by distillation under reduced pressure to obtain an intermediate.

[0034] Step (2), add 2 g of the intermediate and 1.2 g of 4-chloromethylstyrene to 30 mL of acetonitrile, heat to 80° C., stir and react for 18 h, distill under reduced pressure, dissolve the product in ethanol and recrystallize to obtain styryl hydroxy quaternary ammonium salt.

[0035] Step (3), add 40g of polylactic acid and 4.8g of styryl hydroxy quaternary ammonium salt to 500mL of chloroform, heat to 50°C, stir to dissolve, and then distill under reduced pressure to remove chloroform, add the mixture and 0.4g of diisopropylbenzene peroxide to a torque rheometer, perform melt grafting at 180°C for 8min, add the cooled product to chloroform, heat to 50°C, stir to dissolve, and then distill under reduced pressure until a large amount of precipitate is precipitated, filter and dry to obtain hydroxy quaternary ammonium salt grafted polylactic acid.

[0036] Step (4), 600g polyethylene resin, 400g hydroxy quaternary ammonium salt grafted polylactic acid, 30g maleic anhydride grafted polyethylene, and 3g antioxidant 1076 are mixed and added into a twin-screw extruder for extrusion granulation. The temperatures of sections 1-7 of the extruder are 125°C, 155°C, 180°C, 175°C, 185°C, 190°C, and 190°C to obtain a degradable and environmentally friendly material.

[0037] Comparative Example 1 Step (1), 750g polyethylene resin, 16g maleic anhydride grafted polyethylene, and 6g antioxidant 1076 are mixed and added into a twin-screw extruder for extrusion granulation. The temperatures of sections 1-7 of the extruder are 125°C, 155°C, 180°C, 175°C, 185°C, 190°C, and 190°C to obtain a degradable and environmentally friendly material.

[0038] Comparative Example 2 Step (1), 750g polyethylene resin, 250g polylactic acid, 16g maleic anhydride grafted polyethylene, and 6g antioxidant 1076 are mixed and added into a twin-screw extruder for extrusion granulation. The temperatures of sections 1-7 of the extruder are 125°C, 155°C, 180°C, 175°C, 185°C, 190°C, and 190°C to obtain a degradable and environmentally friendly material.

[0039] Comparative Example 3 Step (1), 750g polyethylene resin, 250g hydroxy quaternary ammonium salt grafted polylactic acid (prepared according to the method of Example 1), and 6g antioxidant 1076 are mixed and added into a twin-screw extruder for extrusion granulation. The temperatures of sections 1-7 of the extruder are 125°C, 155°C, 180°C, 175°C, 185°C, 190°C, and 190°C to obtain a degradable and environmentally friendly material.

[0040] Comparative Example 4 Step (1), add 1.3 g 4-chloromethylstyrene and 0.9 g N-methyldipropylamine (structural formula: ), heated to 55°C, condensed and refluxed for 6 hours, distilled under reduced pressure, the product was washed with petroleum ether and dried to obtain styryl quaternary ammonium salt. The structural formula is .

[0041] Step (2), add 40g of polylactic acid and 3g of styryl quaternary ammonium salt to 500mL of chloroform, heat to 50°C, stir to dissolve, and then distill under reduced pressure to remove chloroform, add the mixture and 0.25g of diisopropylbenzene peroxide to a torque rheometer, perform melt grafting at 185°C for 5min, add the cooled product to chloroform, heat to 50°C, stir to dissolve, and then distill under reduced pressure until a large amount of precipitate is precipitated, filter and dry to obtain quaternary ammonium salt grafted polylactic acid.

[0042] Step (3), 750g polyethylene resin, 250g quaternary ammonium salt grafted polylactic acid, 16g maleic anhydride grafted polyethylene, and 6g antioxidant 1076 are mixed and added into a twin-screw extruder for extrusion granulation. The temperatures of sections 1-7 of the extruder are 125°C, 155°C, 180°C, 175°C, 185°C, 190°C, and 190°C to obtain a degradable and environmentally friendly material.

[0043] The degradable and environmentally friendly material was molded on a flat vulcanizer at a temperature of 190°C, a pressure of 10 MPa, and a time of 5 minutes to produce a standard test specimen.

[0044] The tensile properties are tested according to GB / T 1040.1-2018. The flexural strength is tested according to GB / T 9341-2008.

[0045] The antibacterial property was tested according to the method of QB / T 2591-2003, and the test bacteria were Escherichia coli and Staphylococcus aureus. The degradable environmentally friendly material of Comparative Example 1 was used as a blank control sample. The degradable environmentally friendly materials of Examples 1-3 and Comparative Examples 2-4 were used as antibacterial plastic samples.

[0046] Antibacterial rate R=(BC) / B×100%.

[0047] B is the average number of recovered bacteria in the blank control sample (cfu / piece). C is the average number of recovered bacteria in the antibacterial plastic sample (cfu / piece).

[0048] The test results are shown in Table 1.

[0049] Table 1: Effect test

[0050] As shown in Table 1, in Examples 1-3, polyethylene resin and hydroxyl quaternary ammonium salt grafted polylactic acid are used as material matrix. In the process of extrusion melt blending, hydroxyl quaternary ammonium salt grafted polylactic acid contains a large amount of hydroxyl groups, which can react with the anhydride groups of maleic anhydride grafted polyethylene, so that maleic anhydride grafted polyethylene can be used as a compatibilizer to improve the compatibility between hydroxyl quaternary ammonium salt grafted polylactic acid and polyethylene resin, so that the degradable environmentally friendly material formed by polyethylene and polylactic acid has higher mechanical properties, showing better tensile strength and flexural strength. In addition, hydroxyl quaternary ammonium salt grafted polylactic acid contains diquaternary ammonium salt antibacterial groups, which significantly improves the antibacterial rate of degradable environmentally friendly materials to Escherichia coli and Staphylococcus aureus, showing good antibacterial properties.

[0051] In Comparative Example 1, no hydroxy quaternary ammonium salt was added to graft polylactic acid, and the tensile strength and flexural strength of the material were poor.

[0052] The polylactic acid added in Comparative Example 2 does not contain a large amount of hydroxyl groups, and is difficult to react with maleic anhydride grafted polyethylene. Maleic anhydride grafted polyethylene cannot act as a compatibilizer, and cannot improve the compatibility between polylactic acid and polyethylene resin, resulting in the tensile strength and bending strength of the material being lower than those in Example 1. In addition, polylactic acid does not contain quaternary ammonium salt antibacterial groups, and the material does not have antibacterial properties.

[0053] In Comparative Example 3, no maleic anhydride grafted polyethylene was added, and the compatibility between the polyethylene resin and the hydroxy quaternary ammonium salt grafted polylactic acid was poor, and the tensile strength and flexural strength of the material were lower than those in Example 1.

[0054] Comparative Example 4 uses 4-chloromethylstyrene to react with N-methyldipropylamine to obtain a styryl quaternary ammonium salt containing no hydroxyl group, which is then melt-grafted with polylactic acid. The obtained quaternary ammonium salt-grafted polylactic acid does not contain hydroxyl groups and cannot be grafted with maleic anhydride polyethylene, resulting in poor compatibility between the quaternary ammonium salt-grafted polylactic acid and the polyethylene resin. The tensile strength and flexural strength of the material are lower than those in Example 1, and the antibacterial rate is also significantly lower than that in Example 1. It may be that the styryl quaternary ammonium salt contains only one quaternary ammonium salt antibacterial group, and the antibacterial performance is lower than that of the styryl hydroxyl quaternary ammonium salt with a double quaternary ammonium salt group in Example 1.

[0055] The above describes some embodiments of the present invention, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A degradable and environmentally friendly material, characterized in that: The degradable environmentally friendly material comprises 60-75 parts by weight of polyethylene resin, 25-40 parts by weight of hydroxy quaternary ammonium salt grafted polylactic acid, 1.6-3 parts by weight of maleic anhydride grafted polyethylene, and 0.3-0.6 parts by weight of antioxidant; The preparation method of hydroxy quaternary ammonium salt grafted polylactic acid comprises: adding polylactic acid and styryl hydroxy quaternary ammonium salt into chloroform, heating and stirring to dissolve, removing chloroform by reduced pressure distillation, adding the mixture and dicumyl peroxide into a torque rheometer, performing melt grafting, adding the cooled product into chloroform, heating and stirring to dissolve, performing reduced pressure distillation until a large amount of precipitates are precipitated, filtering and drying to obtain hydroxy quaternary ammonium salt grafted polylactic acid; The structural formula of the styryl hydroxy quaternary ammonium salt is as follows: .

2. The degradable environmentally friendly material according to claim 1, characterized in that: The masses of the styryl hydroxy quaternary ammonium salt and dicumyl peroxide are 3-12% and 0.2-0.1% of the mass of the polylactic acid respectively.

3. The degradable environmentally friendly material according to claim 2, characterized in that: The temperature during the melt grafting is 175-185° C. and the time is 5-10 minutes.

4. The degradable and environmentally friendly material according to claim 1, characterized in that: The preparation method of the styryl hydroxy quaternary ammonium salt comprises: Step (1), adding 2,3-epoxypropyltrimethylammonium chloride and diethanolamine to ethanol, stirring for reaction, and then distilling under reduced pressure to remove low-boiling substances to obtain an intermediate; Step (2), adding the intermediate, 4-chloromethylstyrene, to acetonitrile, stirring for reaction and then distilling under reduced pressure, dissolving the product in ethanol for recrystallization, and obtaining styryl hydroxy quaternary ammonium salt.

5. The degradable and environmentally friendly material according to claim 4, characterized in that: In the step (1), the mass of diethanolamine is 70-78% of 2,3-epoxypropyltrimethylammonium chloride.

6. The degradable and environmentally friendly material according to claim 4, characterized in that: In the step (1), the reaction temperature is 45-60°C and the reaction time is 6-12h.

7. The degradable and environmentally friendly material according to claim 4, characterized in that: In the step (2), the mass of 4-chloromethylstyrene is 60-75% of the mass of the intermediate.

8. The degradable and environmentally friendly material according to claim 4, characterized in that: In the step (2), the reaction temperature is 70-80°C and the reaction time is 18-24h.

9. A method for preparing a degradable and environmentally friendly material according to any one of claims 1 to 8, characterized in that: The preparation method comprises: mixing polyethylene resin, hydroxyl quaternary ammonium salt grafted polylactic acid, maleic anhydride grafted polyethylene and antioxidant, adding the mixture into a twin-screw extruder for extrusion granulation, wherein the temperature of the extruder sections 1-7 is 125-190° C., and obtaining a degradable and environmentally friendly material.

10. A cosmetic packaging bottle made of degradable and environmentally friendly material prepared using the degradable and environmentally friendly material obtained by the preparation method of claim 9.

Citation Information

Patent Citations

  • A high-expansion-ratio polylactic acid alloy foam material and its preparation method

    CN107722581B

  • Formable polylactic resin composition and preparation method for plastic strip thereof

    CN101875764A

  • Preparation method of antibacterial degradable film and antibacterial degradable film

    CN114395151A

  • Antibacterial food packaging film and preparation method thereof

    CN115926297A

  • Easily biodegradable polyethylene and preparation method thereof

    CN116478495A

Cited By

  • Waste grease-based emulsifier and preparation method thereof

    CN120535480A

  • Waste oil-based emulsifier and preparation method thereof

    CN120535480B